Assessment of risk scoring of non-communicable diseases among doctors in a medical college of Navi Mumbai: a cross sectional study - Ramaswamy, Sudarshan; Joshi, Sumedha M.; Velankar, Deepa H.; Gosavi, Jayesh D. (International Journal Of Community Medicine And Public Health, 2019)
Background: Doctors are supposed to lead healthier lifestyles and are usually assumed to have lower morbidity and mortality rates than general population due to their medical knowledge. However, recently a study conducted by the research cell of Indian Medical Association (IMA) concluded that doctors die younger and mostly due to cardiovascular diseases. Methods: A cross sectional study was conducted among 100 doctors in a medical college for duration of 3 months. Questionnaires were distributed, they were personally interviewed and required clinical examination was done. Data obtained was tabulated in MS Excel and analyzed using SPSS software. Risk of cardiovascular diseases, diabetes, stroke and obesity was estimated and its association with various determinants was seen. Results: Odds of having central obesity increases 10 times with BMI ≥25 kg/m2 as compared to <25 kg/m2. With risk ratio of 1.96, doctors are twice at risk of having BMI ≥25 as compared to general population. Number of people with higher risk of CVD increased after 45 years of age. People with at least one NCD outnumbered the people without any NCD, in the age group of 45-54 years and above. Insufficient physical activity is prevalent among 37% in this age group. Conclusions: This study gives an idea on impact of medical profession on lifestyle, outlook and attitude towards personal health among professional doctors. Initiatives must be taken to identify the causes of professional stress among doctors and measures must be taken to prevent them.